Physiotherapy and associated factors affecting mouth opening changes in noma patients during initial hospitalization at an MSF-supported hospital in Northwest Nigeria-A retrospective cohort study. - Oluwole Victor Oluwalomola; Emily Briskin; Michael Olaleye; Joseph Samuel; Bukola Oluyide; Mark Sherlock; Adeniyi Semiyu Adetunji; Mohana Amirtharajah (Public Library of Science (PLoS), 2023)
Noma is a rapidly progressing infection of the oral cavity, which can cause the disintegration of the cheek, nose and eye, in under a week. One of the most disabling sequelae is trismus, the restriction of mouth opening, which results in difficulties in speech, mastication, social feeding habits and maintenance of oral hygiene. Restriction of mouth opening among noma patients mostly begins during the transition between World Health Organisation (WHO) stage 3 (gangrene) and stage 4 (scarring) of the disease. This study aims to describe the impact of physiotherapy in noma patients hospitalised with stages 3 and 4 of the disease and to identify factors that influence change in mouth opening of noma patients. This study is a retrospective analysis of routinely collected data from patients admitted at Noma Children Hospital, Sokoto, Northwest Nigeria between 1 May 2018 and 1 May 2020. Eligible patients included stage 3 and 4 noma patients who had not undergone any surgical reconstruction or trismus release surgery but received physiotherapy assessment and treatment during initial hospitalization. Factors associated with a change in mouth opening were identified using paired t-test analysis, bivariate and multivariate analyses. The mean difference in the mouth opening from admission to discharge was 6.9mm (95% CI: 5.4 to 8.3, p < 0.0001). Increased number of physiotherapy sessions and patient age above three years were significant predictors of improvement in mouth opening (p-value 0.011, 0.001 respectively). Physiotherapy treatment received within an adequate number of physiotherapy sessions for stage 3 and 4 noma patients during the period of the first hospitalization is important and results in a significant increase in mouth opening. Hence, noma patients at these stages should routinely undergo physiotherapy as part of a holistic approach to treatment.